Exploring promising diversity in acid lime - Mishra, D S; Singh, Sanjay; Singh, A K; Yadav, Vikas; Rao, V V Appa (Indian Horticulture, 2019)
There is a wide genetic diversity in growth habit, leaf morphological characters, bearing habit, fruit physico-chemical characters and incidence of citrus canker in acid lime, offering immense opportunity to explore germplasm for superior genotypes from existing population growing under semi-arid climatic conditions of central Gujarat. Genetic diversity in acid lime has got immense potential to raise quality fruit production and productivity, yet the conservation and use of these genotypes have not yet been carried out extensively. In absence of identification, conservation and utilization of indigenous acid lime genotypes, losses of such valuable genotypes occurs and will continue to occur. Therefore, identification of elite valuable genotypes, their proper use and conservation of these valuable unique resources is essential to increase quality production for domestic consumption and export. The acid lime germplasm were explored for exsitu conservation and characterization at CHES, Godhra. Some of the local genotypes of acid lime were elite and these genotypes could be recommended for commercial cultivation after evaluation.